(untitled) - LaFeber, Walter (Boston, Mass., 1988)
THE AMERICAN CENTURY is a succinct, well-written history of the United States in the modern (post-1890s) era. It is valuable for either the second half of U.S. survey courses or for 20th Century U.S. courses for upperclass students. The text places special emphasis on economic and urban growth, social and political change, civil rights and liberties, and the growth of the U.S. into a global superpower
Keywords: United States; History